Meningeal inflammation as a driver of cortical grey matter pathology and clinical progression in multiple sclerosis - Owain Howell (Nature Reviews Neurology, 2023)
Growing evidence from cerebrospinal fluid samples and post-mortem brain tissue from individuals with multiple sclerosis (MS) and rodent models indicates that the meninges have a key role in the inflammatory and neurodegenerative mechanisms underlying progressive MS pathology. The subarachnoid space and associated perivascular spaces between the membranes of the meninges are the access points for entry of lymphocytes, monocytes and macrophages into the brain parenchyma, and the main route for diffusion of inflammatory and cytotoxic molecules from the cerebrospinal fluid into the brain tissue. In addition, the meningeal spaces act as an exit route for CNS-derived antigens, immune cells and metabolites. A number of studies have demonstrated an association between chronic meningeal inflammation and a more severe clinical course of MS, suggesting that the build-up of immune cell aggregates in the meninges represents a rational target for therapeutic intervention. Therefore, understanding the precise cell and molecular mechanisms, timing and anatomical features involved in the compartmentalization of inflammation within the meningeal spaces in MS is vital. Here, we present a detailed review and discussion of the cellular, molecular and radiological evidence for a role of meningeal inflammation in MS, alongside the clinical and therapeutic implications.